2021
DOI: 10.2217/pgs-2021-0061
|View full text |Cite
|
Sign up to set email alerts
|

Is Olaparib Cost Effective in Metastatic Castration-Resistant Prostate Cancer Patients with at Least one Favorable Gene Mutation in BRCA1 , BRCA2 or ATM ?

Abstract: Aim: To compare the cost–effectiveness of olaparib versus control treatment in metastatic castration-resistant prostate cancer patients with at least one gene mutation in BRCA1, BRCA2 or ATM from the US payer perspective. Methods: A Markov model was constructed to assess the quality-adjusted life years (QALYs) and incremental cost–effectiveness ratios. Sensitivity analyses and scenario analyses were conducted to explore the impact of uncertainties. Results: The base-case result indicated that, for patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…PARPi evaluated in these studies included olaparib [ 16 – 18 , 20 22 , 25 28 , 30 32 , 34 40 ], niraparib [ 18 20 , 23 , 26 , 28 ], rucaparib [ 20 , 28 ], talazoparib [ 33 ], and veliparib [ 24 ]. Modeling methods employed included the Markov model (n = 11) [ 16 , 21 , 22 , 24 , 28 , 30 , 32 , 36 , 37 , 39 , 40 ], decision tree model (n = 6) [ 17 20 , 23 , 35 ], partitional survival model (n = 7) [ 25 , 27 , 31 , 33 , 34 , 38 ], and the non-Markov alternatives (n = 1) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…PARPi evaluated in these studies included olaparib [ 16 – 18 , 20 22 , 25 28 , 30 32 , 34 40 ], niraparib [ 18 20 , 23 , 26 , 28 ], rucaparib [ 20 , 28 ], talazoparib [ 33 ], and veliparib [ 24 ]. Modeling methods employed included the Markov model (n = 11) [ 16 , 21 , 22 , 24 , 28 , 30 , 32 , 36 , 37 , 39 , 40 ], decision tree model (n = 6) [ 17 20 , 23 , 35 ], partitional survival model (n = 7) [ 25 , 27 , 31 , 33 , 34 , 38 ], and the non-Markov alternatives (n = 1) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, evaluating the cost-utility scores of olaparib from the perspective of pharmacoeconomics is of great significance, though there are few studies on the cost-utility scores of olaparib in treating mCRPC. From the perspective of United States payers, Li et al ( 21 ) evaluated the cost-utility scores of olaparib in treating mCRPC patients with BRCA1, BRCA2, or ATM mutation, and the results showed that the cost and utility of olaparib treatment were $157,732 and 1.26 QALYs, respectively. Compared with the control group, the ICER of olaparib was $248,248/QALY.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 The economics of adopting such an approach, however, is not clear. Our search strategy led us to two studies 19,24 on the cost-effectiveness of genetic test-directed treatment with the PARP inhibitor, Olaparib in men with mCRPC. However, the setting for both studies were men who tested positive for three or 15 pre-specified gene alterations i.e., both the intervention group (olaparib therapy) and the comparator (standard care) were men who were variant positive.…”
Section: Discussionmentioning
confidence: 99%
“…However, the setting for both studies were men who tested positive for three or 15 pre-specified gene alterations i.e., both the intervention group (olaparib therapy) and the comparator (standard care) were men who were variant positive. It was not possible to examine the cost-benefits of a germline testing versus no testing scenario and both studies 19,24 were excluded from the review. Overall, the evidence on cost-effectiveness of germline testing in prostate cancer is limited, therefore policy advice for testing in this cancer group is not yet possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation